2016
DOI: 10.1017/ice.2016.273
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak ofKlebsiella pneumoniaeCarbapenemase–ProducingCitrobacter freundiiat a Tertiary Acute Care Facility in Miami, Florida

Abstract: OBJECTIVE To describe the investigation and control of a rare cluster of Klebsiella pneumoniae carbapenemase-producing Citrobacter freundii in a hospital in southern Florida. METHODS An epidemiologic investigation, review of infection prevention procedures, and molecular studies including whole genome sequencing were conducted. RESULTS An outbreak of K. pneumoniae carbapenemase-3-producing C. freundii was identified at a tertiary hospital in Florida in 2014. Of the 6 cases identified, 3 occurred in the same in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Among them, carbapenem-nonsusceptible Citrobacter spp. (CNSC) have become increasingly recognized as health care-associated pathogens ( 9 13 ). CNSC isolates have been found to be both genotypically and phenotypically diverse ( 14 , 15 ), and their resistance to carbapenems is frequently caused by plasmid-borne carbapenemase genes, which can be readily acquired through horizontal gene transfer ( 12 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, carbapenem-nonsusceptible Citrobacter spp. (CNSC) have become increasingly recognized as health care-associated pathogens ( 9 13 ). CNSC isolates have been found to be both genotypically and phenotypically diverse ( 14 , 15 ), and their resistance to carbapenems is frequently caused by plasmid-borne carbapenemase genes, which can be readily acquired through horizontal gene transfer ( 12 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…; very few studies have reported C. freundii producing VIM or KPC. [4][5][6][7][8] Some Enterobacteriaceae species, such as Citrobacter spp. J Antimicrob Chemother 2017; 72: 3283-3287 doi:10.1093/jac/dkx325 Advance Access publication 27 September 2017 or Enterobacter spp., often present decreased susceptibility to carbapenems, mainly ertapenem, due to the overproduction of chromosomal AmpC b-lactamase plus reduced outer membrane permeability; 9 as a consequence, production of carbapenemases in these species may be underdiagnosed in clinical microbiology laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Citrobacter spp. have become increasing recognized as a cause of multidrug-resistant healthcare-associated infections around the world (10, 4244), and prior reports have identified CNSC predominantly from healthcare sources and often associated with nosocomial outbreaks (9, 12, 45). We detected a significant increase in the proportion of Citrobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, carbapenem-non-susceptible Citrobacter spp. (CNSC) have become increasingly recognized as a healthcare-associated pathogen (913). CNSC isolates have been found to be both genotypically and phenotypically diverse (14, 15), and their resistance to carbapenems is frequently caused by plasmid-encoded carbapenemases, which can be readily acquired through horizontal gene transfer (12, 16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation